Attitudes towards Refugees in the Political Center of Germany: A Re-Analysis. (20th October 2021) - Boege, R; Budde, S; Rees, J; Zick, A
Abstract: The German political center is often viewed as democratic and moderate, untouched by right-wing outsiders. Evident right-wing terrorism was often treated as a peripheral phenomenon. In 2015, the peak of the refugee movement constituted a challenge for that German political center and was vividly discussed in the media. Expressions such as "refugee wave" or "crisis" dominated the public discussion. These expressions could spur on Othering processes because not only do these expressions carry a negative valence, but they also put a spotlight on categorial ascriptions. Between 2014 and 2018, attacks on refugee shelters in Germany multiplied by five, and votes for right-wing populist parties rose in Europe. The center studies are representative studies that regularly assess right-wing attitudes in the German political center since 2006. In a re-analysis, we investigated attitudes towards refugees in specific. From three studies, run in 2014, 2016, and 2018/19 (total N = 6, 021), relevant questions and questionnaires were identified via word stem search. Fourteen scales were deemed as relevant for attitudes towards refugees, including attitudes towards migration and perceived sayability, group-focused enmity, social dominance orientation, and right-wing authoritarianism. Correlations between the participants' self-categorization as German and European with rejecting attitudes toward refugees are discussed. Further, demographic information was used to assess the distribution of (non-)rejecting attitudes towards refugees depending on region, income, and education. The development of these attitudes and their correlations with other attitudes will be presented. Whilst manifest right-wing attitudes are rare in the German center, aspects of rejection of refugees are shared by up to a third of the participants. Implications for Othering as an iterative process will be discussed.